DETERMINAN FERTILITAS PEKERJA WANITA SEKTOR FORMAL DI KECAMATAN DENPASAR SELATAN - Ida Ayu Mas Pramesthi Dharma Dewi Manuaba; Anak Agung Istri Ngurah Marhaeni (E-Jurnal Ekonomi Pembangunan, 2023)
The aims of this study were to analyze the effect of family income, education, desired number of children and preference on the sex of the child on the duration of contraceptive use by women in the formal sector; analyzing the effect of family income, education, desired number of children, preference on the sex of the child, and duration of contraceptive use on the fertility of women workers in the formal sector; analyzing the role of duration of contraceptive use in mediating the effect of family income, education, the number of children desired, and preference on the sex of the child on the fertility of formal sector women workers. The type of data used is quantitative and qualitative data. Data collection used the method of observation, structured interviews and in-depth interviews with 60 respondents. The results showed the family income and education of the respondents had a positive and significant effect. The number of children desired and preference for the sex of the child have a negative and significant effect on the length of use of contraceptives; the number of children desired and preference on the sex of the child has a positive and significant effect.